A Retrospective Analysis of a Cohort of Patients Treated With Immune Checkpoint Blockade in Recurrent/Metastatic Head and Neck Cancer - Bila, Michel; Van Dessel, Jeroen; Smeets, Maximiliaan; Vander Poorten, Vincent; Nuyts, Sandra; Meulemans, Jeroen; Clement, Paul M. (Frontiers in Oncology, 2022)
Objective The treatment approach of recurrent or metastatic head and neck squamous cell carcinoma (R/M HNSCC) has long been similar for all patients. Any difference in treatment strategy was only based on existing comorbidities and on preferences of the patient and the treating oncologist. The recent advance obtained with immune therapy and more specifically immune checkpoint blockade (ICB) has been a true game changer. Today, patients and physicians have a choice to omit chemotherapy. In a small subset of patients, ICB induces a very durable disease control. The subgroup of patients in which ICB without chemotherapy would be the preferential approach is still ill-defined. Yet, this evolution marks a major step towards a more personalized medicine in R/M HNSCC. Materials and Methods In this paper, we present a retrospective cohort study of a patient population that was treated with ICB in a single center and we analyze potential factors that are associated with outcome and may help to select patients for treatment with ICB. Results 137 consecutively treated patients were identified. Male gender and metastatic disease appeared to be associated with improved overall survival (OS). There was no correlation observed with age, number of previous treatment lines or immune target. Conclusion Along with PD-L1 status defined by Combined Positive Score (CPS), clinical parameters such as site of recurrence and gender may help to define the optimal treatment strategy in R/M HNSCC.